What is the Effect of Contemporary Financial Concepts on Business Performances of the Serbian Companies? - Vjetrov, Ana; Barjaktarovic, Lidija; Dimic, Maja (Industrija, 2019)
The main focus of this paper is the analysis of the implementation of modern financial concepts such as NPV, IRR etc. in everyday business activities of the Serbian companies. The aim of the paper is establishing the link between the implementation of contemporary financial concepts and profitability of the company, quantified by Net profit, using binary logistic regression. The implementation will be investigated, using the sample of 65 companies and questionnaires sent to the CFOs (chief financial directors) within the period from 2015 till 2018. Two surveys were conveyed within the above-mentioned period 1) Analysis of the responses of 65 financial executives within the period from 2015 to 2018 and 2) Analysis of profitability indicators of the companies in the sample, acquired from relevant documents such as Balance Sheet, Income Statement, Notes to the Financial Statements and Annual Business Reports within the period from 2015 till 2018. The research conveyed confirms that well defined investment policy with implementation of the suitable investment criteria, positively influence on business performance of the companies in Serbia. However, for successful business performances pure technical knowledge is not enough -Flexibility and adaptability of managers is gaining the growing importance within ever changing economic environment.
Keywords: Net Profit; Profitability; PP; NPV; Capital Budgeting Techniques; Capital budgeting